Phytochemical analysis, cytotoxic and in vitro antioxidant activity of erythrina variegate bark - Shahriar, Mohammad; Khair, Nishat Zareen; Sheikh, Zara; Chowdhury, Sayeeda Fahmee; Kamruzzaman, Md.; Bakhtiar, Md. Shawkatul Islam; Chisty, Sharmin Jahan; Narjish, Syeda Najah; Akhter, Rumana; Akter, Nahia (© 2015 European Journal of Medicinal Plants, 2016)
This article was published in the European Journal of Medicinal Plants [©2015 European Journal of Medicinal Plants] The Article's website is at: http://www.journalrepository.org/media/journals/EJMP_13/2015/Nov/Shahriar1132015EJMP18866.pdf